2016
DOI: 10.1111/resp.12958
|View full text |Cite|
|
Sign up to set email alerts
|

Nasal lavage, blood or sputum: Which is best for phenotyping asthma?

Abstract: Background and objective: Determination of asthma phenotypes, particularly inflammatory phenotypes, helps guide treatment and management of this heterogeneous disease. Induced sputum cytology has been the gold standard for determination of inflammatory phenotypes, but sputum induction is fairly invasive and technically challenging. Blood and nasal lavage cytology have been suggested as substitutes, but have not been fully verified. The aim of this study is to determine the accuracy of blood and nasal lavage cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
3
16
0
1
Order By: Relevance
“…is remarkably similar to a number of other large cohorts and the largest study of more than 500 adults showed blood eosinophils to be independent predictor of sputum eosinophilia . Sensitivity of blood eosinophils to predict sputum eosinophilia seems to vary significantly, with the study of De Farias et al . observing a much lower sensitivity around half of that reported in the other studies.…”
supporting
confidence: 87%
See 3 more Smart Citations
“…is remarkably similar to a number of other large cohorts and the largest study of more than 500 adults showed blood eosinophils to be independent predictor of sputum eosinophilia . Sensitivity of blood eosinophils to predict sputum eosinophilia seems to vary significantly, with the study of De Farias et al . observing a much lower sensitivity around half of that reported in the other studies.…”
supporting
confidence: 87%
“…By comparison, blood eosinophils had a lower specificity (72%) for identifying eosinophilic asthma and therefore a lower area under the curve following receiver operator curve (ROC) analysis. The specificity of blood eosinophils reported by De Farias et al . is remarkably similar to a number of other large cohorts and the largest study of more than 500 adults showed blood eosinophils to be independent predictor of sputum eosinophilia .…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Blood cell count is often used as a substitute for sputum cytology to identify inflammatory phenotypes in asthma. de Farias et al . reported that nasal lavage cytometry showed better accuracy than blood cell count for characterizing asthma inflammation and recommended the use of nasal lavage cytology as an easy and accurate substitute for induced sputum cytology.…”
Section: Asthmamentioning
confidence: 99%